A facile approach to synthesize azaindoline functionalized spirocarbocyclic scaffolds via a Pd-catalyzed cascade cyclization/dearomatization process. Issue 22 (12th October 2018) - Wu, Xin-Xing; Tian, Hui; Wang, Yu; Liu, Anjia; Chen, Hengfan; Fan, Zhixiang; Li, Xuefeng; Chen, Shufeng
Abstract : Azaindoline functionalized spirocarbocyclic scaffolds bearing two all-carbon quaternary centers are synthesized. Abstract : A novel construction of azaindoline functionalized spirocarbocyclic scaffolds bearing two all-carbon quaternary centers has been developed via a palladium-catalyzed Heck cyclization/phenol dearomatization reaction. In the cascade process, three new C(sp 2 )–C(sp 3 ) bonds are formed in a single chemical operation. The approach shows broad substrate scope and good functional-group tolerance.